Efficacy of Combination Dutasteride and Lycopene to Reduce Bleeding in Benign Prostate Hyperplasia (BPH) Post- Transurethral Resection of the Prostate (TURP) Overview of Hypoxia inducible factor-1 alpha (HIF-1 α) Expression and Hematocrit Levels - Eriawan Agung Nugroho; Siti Amarwati; Nugroho Akhbar (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Trans Urethral Resection of the Prostate (TURP) is one of the gold operating standards for people with Benign Prostate Hyperplasia (BPH), but the complications, like bleedings, often occur both in durante and post-surgery. The risk of bleeding in TURP is caused by angiogenesis. Hypoxia-Induced Factor-1 Alpha (HIF-1 α) is one of the trigger factors for angiogenesis in BPH. Based on the existing literature, it was found that there was a relationship between lycopene and dutasteride which both had a synergistic effect in inhibiting angiogenesis. However, the mechanism is unknown. This study aims to assess the effectiveness of the combination of dutasteride and lycopene on the expression of HIF-1α and hematocrit levels in BPH patients undergoing TURP surgery. This research was an experimental study with